The Effect Number of Pebax® 1657 Coating Layer on Thin Film Composite (TFC) Membrane for CO2/N2 Separation - Mohamad Syafiq, Abdul Wahab; Sunarti, Abd Rahman (Chiangmai University, 2018)
A high performance of thin film composite (TFC) membrane was fabricated with Pebax® 1657 as a selective layer on top of PVDF substrate to improve the CO2/N2 separation. The purpose of the studies was to investigate the effect of Pebax® 1657 coating layer to the permeability and selectivity. The substrate was produced by using 15% of PVDF diluted in 85% of NMP as a dope solution. Meanwhile, the Pebax® 1657 was diluted in 70/30 ethanol water which later acts as a selective layer to the substrate. The number of layer varies by 1,2,3 and 4 which gave different thickness of Pebax® 1657- 0.002mm, 0.004mm, 0.011mm and 0.018mm respectively. The FTIR analysis was done for chemical analysis for the produced TFC membrane. The SEM image revealed that the PVDF pore ranging from 930nm to 1.8 μm with large finger like void was formed and it was believed that the formation of pores and void due to the solvent-non solvent interaction during film bath. The 3 layer Pebax® 1657 gave the highest selectivity of 13.69, 2 bar with CO2 and N2 permeance of 29 and 2 respectively whereas at 4 coating layer no gas flow was recorded during the test.